Price Sensitivity of Residential Energy Consumption in Norway - Runa Nesbakken (Statistics Norway, Research Department, 1998)
The main aim of this paper is to test the stability of the results of a model which focus on the relationship between the choice of heating equipment and the residential energy consumption. The results for the income and energy price variables are of special interest. Stability in the time dimension is tested by applying the model on micro data for each of the years 1993, 1994 and 1995. The parameter estimates are stable within a 95 per cent confidence interval. However, the estimated impact of the energy price variable on energy consumption is considerably weaker in 1994 than in 1993 and 1995. The results for two different income groups in the pooled data set are also subject to stability testing. The energy price sensitivity in residential energy consumption is found to be higher for high-income households than for low-income households.
Keywords: C52; D12; Q41; 330; Household energy consumption; space heating system; discrete-continuous choice; parameter stability.